Performance of Male Bali Duck that Was Given Probiotic through Drinking Water - I G. G. Y., Pradana; Siti, N W.; Ardika, I N. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of giving effective microorganism probiotics through drinking water to the performance of male bali ducks. The study was conducted in Kediri, Tabanan foreight weeks starting from August 2 to October 2, 2018. The design used was a Completely Randomized Design (CRD) consisting of three treatments, namely: P0 (drinking water without the addition of probiotics as a control), P1 (drinking water + probiotics 0.5%), and P2 (drinking water + probiotics 1%). The observed variables were initial body weight, feed consumption, water consumption,final body weight, weight gain, and Feed Convertion Ratio. The results showed that the consumption of rations in treatments P1 and P2 was not significant (P> 0.05) lower than P0. Drinking water consumption in treatment P1 and P2 was significantly (P <0.05) lower than P0. The final body weight and weight gain at P1 and P2 approval was not significantly (P> 0.05) lower than P0. Drinking water consumption in treatments P1 and P2 were significantly (P <0.05) lower than P0. FCR in P1 treatment was not significantly (P> 0.05) lower than P0 and P2 treatments. Based on the results of the study it can be concluded that the administration of effective microorganism probiotics through drinking water from the level of 0.5% to 1% has no effect on the performance of male bali ducks agedeight weeks.   Keywords: Probiotics, male bali ducks, performance.